Trachygamasus karuni sp. nov., a new mite species from Iran (Parasitiformes: Parasitidae) - Farahi, Sara; Shishehbor, Parviz; Nemati, Alireza; Witaliński, Wojciech (Zootaxa, 2019)
A new mite species, Trachygamasus karuni sp. nov. is described from buffalo, sheep and horse manure at several locations north of Ahvaz city, Khuzestan, Iran. A key to 14 world species of Trachygamasus with described adults is also provided.